User-Perceived Quality and Functional Suitability of Representations of DEMO’s Process and Fact Models: Conclusions From a Family of Three Studies - Dulce Pacheco; David Aveiro; Duarte Pinto; Vitor Freitas (IEEE Access)
Clear and cognitively compelling diagrams representing organizational reality are crucial for structured communication, proper information systems implementation, and ultimately, organizational success. Design and Engineering Methodology for Organizations (DEMO), a standard from the field of Enterprise Engineering, provides representations for Process and Fact Models. However, the complexity of its notations can impede stakeholder understanding. New representations for these models have been proposed, but lacked formal evaluation across diverse user groups. This paper addresses this gap by assessing user perception of both standard and newly proposed DEMO representations. We conducted a family of three evaluation studies using mixed research methods across distinct user groups ( ${N} =32$ ). Results show a unanimous preference for the new representations in terms of perceived quality and functional suitability, supporting most of our hypotheses. Our study does not support the claim that familiarity with the modeling language improves perception of empirical quality. This research expands the knowledge base on the underexplored area of user experience within DEMO models and representations.